ANALISIS KINERJA KEUANGAN PEMERINTAH PROVINSI KALIMANTAN TIMUR TAHUN ANGGARAN 2009 – 2012 - Arief, Arfandi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
The purpose of this investigation is to determine the regional financial performance in East Kalimantan. The initial step in this research was determining the variables used, namely: investment and economic growth. Afterward, collecting the data in the form of secondary data (time series) from 2009-2012 files in order to analyze the regional financial performance and the records from 2000-2012 to analyze the influence of investment and growth. Ultimately, the data was examined using multiple regression analysis. The result showed that the regional financial performance of East Kalimantan occupied the level of “good” in terms of independence, effectiveness, and harmony. Not much different, in terms of growth and proportions, their performance was still at the level of